Percepção de imprevisibilidade familiar e sua relação com a propensão ao risco e o desconto do futuro - Rodrigues, Anna Beatriz Carnielli Howat (2010)
It is proposed that the perception of resource unpredictability during childhood promotes the development of a mental model of unpredictability, precursor of the preference for the immediate attainment of the resource (future discount) and for risk-taking, as a way of maximizing the chances of obtaining those resources perceived as unpredictable. The apparent irrationality of those behaviors (future discount and risk-taking) could be interpreted as adaptive responses to unpredictable environments produced by cognitive mechanisms of information processing on the environment, selected over human evolution. This study aimed to investigate relations between childh od family unpredictability dimensions, risk-taking and future discount. It included 394 people: 158 adults in conflict with the law that had already been in prison (mean age = 34.23 years; sd=10.17), 122 college students (M=19.26; sd=2.06) and 114 women above 40 years old and at least high school concluded (M=51.19; sd=8.64). We hypothesized that perceptions of childhood family unpredictability would favor short term choices and greater risk-taking. We used the procedure of monetary choice to evaluate future discount, the Childhood Family Unpredictability Scale (EIFI) and Specifc Risk-Taking Scale (EPRE), validated for the Brazilian population in the first two papers of this work. Both scales showed factor structure of four factors with satisfactory reliability indexes for research purposes. The results of the third paper indicated partial relation between the constructs of risk-taking and unpredictability, however, low relation of those and future discounting. The groups differed in relation to future discount (ANOVA), risk-taking (removed the effects of income MANCOVA) and family unpredictability (removed the effects of age and income MANCOVA). The group that exhibited the highest means of unpredictability also exhibited higher rates of future discount (adults in conflict with the law), indicating some relationship among these variables, especially in the area of financial resources. Risk-taking variables, however, behaved in an unexpected way with unpredictability and future discount. We concluded, considering the multidimensional approach, that relations among the constructs may not be linear as originally proposed. We indicate the possibility of expanding the study of these relations considering nonlinear models and refinement of evolutionary hypotheses.